Organizational and Economic Mechanisms for Promoting Residential Battery Energy Storage Systems in Ukraine - Trypolska, Galyna; Kurbatova, Tetiana; Kubatko, Oleksandra; Prause, Gunnar; Domashenko, Maryna (International Journal of Energy Economics and Policy, 2024)
Energy storage technologies are one of the ways to decrease the intermittency of renewable energy such as sun or wind. The article aims to consider the organizational and economic mechanisms of promoting residential battery energy storage systems (R-BESS) in Ukraine, as households have ensured the significant growth of installed capacities of residential PV installations, reaching 1.4 GW by 2024. The energy system of Ukraine faces balancing challenges, and partial covering of the demand for energy by households with the help of R-BESS should be beneficial for the energy system. Using methods of levelized cost of electricity and cost of storing electricity, and based on the projected electricity demand and the number of R-BESS, measures were suggested to stimulate the R-BESS installation. Significant investments are required to employ R-BESS, reaching EUR2024 2.9-3.6 billion by 2050. If the interest rates for loans are subsidized, the expenditures on subsidies will reach only EUR2024 35-44 million, and the households themselves must allocate the remainder of the funds.